2010
DOI: 10.1002/joc.2250
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trends and variability in measured multi‐spectral aerosol optical depth over a tropical urban station in India

Abstract: Sun photometer-derived multi-spectral aerosol optical depth (AOD) measurements made at Pune (18°32 N, 73°51 E), India, during the period May 1998-December 2007 have been used to examine possible long-term trends and variability. Long-term mean AOD in the spectral range 380-1020 nm ranged between 0.593 ± 0.11 and 0.220 ± 0.04 with a coefficient of variation (COV) of 34-49%. Day-to-day variations in AOD at all the wavelengths in the range 380-870 nm showed significant long-term increasing trends; the increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 16 publications
1
27
0
1
Order By: Relevance
“…However, in pre-monsoon, a reversal in the SSA variation is observed (SSA is 0.87 ± 0.02 at 440 nm; and 0.89 ± 0.04 at 1020 nm). This suggests that the dominance of coarse particles (mostly dust) during premonsoon, is either due to local activities like urbanization, industrialization and construction activities or wind-blown dust due to strong surface heating (Devara et al, 2002;Devara et al, 2005;Ramachandran and Rajesh, 2007;Bhawar, 2008;Babu et al, 2010;Dani et al, 2010;Kumar et al, 2011). Additionally, long-range transport of dust may also play a role in this regard, for example, aerosols get transported from Saudi Arabia and Afghanistan to the study region (Pandithurai et al, 2007).…”
Section: Single Scattering Albedo (Ssa)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in pre-monsoon, a reversal in the SSA variation is observed (SSA is 0.87 ± 0.02 at 440 nm; and 0.89 ± 0.04 at 1020 nm). This suggests that the dominance of coarse particles (mostly dust) during premonsoon, is either due to local activities like urbanization, industrialization and construction activities or wind-blown dust due to strong surface heating (Devara et al, 2002;Devara et al, 2005;Ramachandran and Rajesh, 2007;Bhawar, 2008;Babu et al, 2010;Dani et al, 2010;Kumar et al, 2011). Additionally, long-range transport of dust may also play a role in this regard, for example, aerosols get transported from Saudi Arabia and Afghanistan to the study region (Pandithurai et al, 2007).…”
Section: Single Scattering Albedo (Ssa)mentioning
confidence: 99%
“…Pandithurai et al (2007) observed seasonal diurnal asymmetry in aerosol optical properties over Western India. Dani et al (2010Dani et al ( ) studied long-term (1998Dani et al ( -2007 AOD variations over Pune and found significant long-term increasing trend. They observed dominance of smaller size particles during winter and coarse-mode particles during pre-monsoon.Over Indore, Gupta et al (2003) also found low AOD during winter and high AOD during pre-monsoon.…”
Section: Introductionmentioning
confidence: 99%
“…Koukouli et al [3] showed a negative trend in AOD over the Southern Balkan/Eastern Mediterranean region, where the highest annual decreasing rate is 4.09% for the summer months and the lowest 2.55% for the winter months. Dani et al [4] observed an increasing AOD trend of 380 nm at 45% per decade at Pune, India, during May 1998-December 2007. In addition, long-term increasing trends in Angstrom wavelength exponent (Alpha) and mean turbidity coefficients of 25.3% and 8.4% per decade is revealed respectively, which indicates that fine-mode aerosols have been increasingly added to the atmosphere over urban regions due to increases in urbanization and human activity.…”
mentioning
confidence: 99%
“…Similarly, higher value of Ångström exponent in winter season compared to the pre-monsoon season with increasing trends of 25.3% per decade has been reported over Pune, India [22] . Trajectory (NOAA-HYSPLIT) model [23] , 5-day isentropic air mass back concentration weighted trajectories are computed to find out the probable flow paths and source regions of air flow with time over Bongaigaon.…”
Section: Resultsmentioning
confidence: 66%